UNRAVELING THE COMPLEXITIES AND VERSATILITY OF HYPERSPECTRAL IMAGING APPLICATIONS - Samuel, M (International Journal of Allied Sciences (IJAS), 2022)
Hyperspectral Imaging (HSI) is a sophisticated technique that has emerged as a valuable tool in providing rich data on spectral, spatial, and temporal aspects of various subjects. By fusing the principles of spectroscopy and imaging, HSI excels in segmenting and recognizing regions of interest through the analysis of spectral values. Over the years, its appeal has grown exponentially, finding applications in diverse areas such as remote sensing, agriculture, medicine, astronomy, surveillance, food quality evaluation, and pollution monitoring. This growth is primarily driven by the ability of HSI to extract valuable information from spectral signatures present in complex scenes. In this article, we aim to provide a comprehensive overview of hyperspectral imaging, its underlying concepts, and its increasing influence across different application domains, emphasizing the immense potential of this cutting-edge technology.